An Overview of the Mjølner BETA System - Bak, Lars; Nørgaard, Claus; Knudsen, Jørgen Lindskov; Madsen, Ole Lehrmann (DAIMI Report Series, 1991)
The Mjølner BETA System is an integrated and interactive programming environment with support for industrial object oriented programming. The Mjølner BETA System is a result of the Scandinavian research project Mjølner. The integration of the various tools in the Mjølner BETA System is established by insisting that all tools in the system utilizes on single representation of the program. This representation is abstract syntax trees (ASTs). All manipulations of the ASTs by the various tools are done utilizing the metaprogramming system which defines an interface to the AST and ways to manipulate the AST.